JAMINAN SOSIAL ATAS SERANGAN JANTUNG SEBAGAI KECELAKAAN KERJA DITINJAU DARI UNDANG UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Maria Angela Triwidyarti; Gunardi Lie; Moody R. Syailendra (Jurnal Hukum Adigama, 2021)
This studi discusses social security for heart attacks as work accidents in term of Law Number 13 of 2003 concerning Employment. This study uses normtive legal research method with a descriptive reseacrh nature. From this research, there are problems regarding social security for work accidents and the risk of heart attack as work accident based on law number 13 of 2003 concerning employment. Employment issues are still crucial issues and are concern to various parties. The state of Indonesia as a state of law of course all applicable provisions relating to laws and regulations. The most highlighted is about social security. Social security the right of every citizen which is the responsibiliy of the state. Social security is a right for every citizen, especially BPJS Ketenagakerjaan Participants. Everyone who has a work accident has the right to get a work accident Insurance (JKK). That everyone without exception and without discrimination has the right to get social securuty as determined by the applicable law. Social security is from citizen.